Efficiency Gains in Unsuccessful Management Buyouts - Ofek, Eli (Journal of Finance, 1994)
This article uses a sample of 120 unsuccessful management buyouts (MBOs) to test whether operational improvements following successful MBOs are a result of organizational changes or private information. The findings are consistent with the organizational changes hypothesis. Firms with an unsuccessful MBO had no increase in operating performance following the buyout attempt. In addition, the cumulative abnormal stock return from before the attempted buyout until two years after the attempt is insignificantly different from 0 percent. I also find that management turnover following an unsuccessful MBO is significantly higher than normal.